The Impact of Liquidity Strategy on Banking Performance in the ASEAN Region - Safitri, Julia; Geraldina, Ira (Indonesian Journal of Business Analytics, 2024)
Banking as one of the financial institutions in Indonesia is required by its owners and shareholders to have good performance to increase company value on an ongoing basis. To improve performance, companies must be able to analyze risks that may occur by implementing risk management. The population in this study are banking companies in 6 ASEAN countries, namely, Indonesia, Singapore, Malaysia, Thailand, Vietnam, and the Philippines during the 2019-2022 period. The sample selection technique in this study was purposive sampling of 120 samples with a total of 30 companies. The analysis tool used is SEM-PLS with the WarpPLS 7.0 application. The research results show that the liquidity variable measured using the Liquidity Coverage Ratio (LCR) has a significant effect on the company's performance as measured using Tobin'Q. Furthermore, the capital adequacy variable which is measured using the Capital Adequacy Ratio (CAR) as a moderating variable explains that CAR is not significant/weakens the relationship between LCR and Tobin's Q. This can be explained that liquidity and capital adequacy are two key components that determine the stability and sustainability of operations bank.